Stable carbon and oxygen isotopes in tree rings show physiological responses of Pericopsis elata to precipitation in the Congo Basin. (12th April 2016) - Colombaroli, Daniele; Cherubini, Paolo; De Ridder, Maaike; Saurer, Matthias; Toirambe, Benjamin; Zweifel, Noëmi; Beeckman, Hans
Abstract: In equatorial regions, where tree rings are less distinct or even absent, the response of forests to high-frequency climate variability is poorly understood. We measured stable carbon and oxygen isotopes in anatomically distinct, annual growth rings of four Pericopsis elata trees from a plantation in the Congo Basin, to assess their sensitivity to recorded changes in precipitation over the last 50 y. Our results suggest that oxygen isotopes have high common signal strength (EPS = 0.74), and respond to multi-annual precipitation variability at the regional scale, with low δ 18 O values (28–29‰) during wetter conditions (1960–1970). Conversely, δ 13 C are mostly related to growth variation, which in a light-demanding species are driven by competition for light. Differences in δ 13 C values between fast- and slow-growing trees ( c . 2‰), result in low common signal strength (EPS = 0.37) and are driven by micro-site conditions rather than by climate. This study highlights the potential for understanding the causes of growth variation in P. elata as well as past hydroclimatic changes, in a climatically complex region characterized by a bimodal distribution in precipitation.